2013
DOI: 10.1007/s00284-013-0466-7
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Inherent Homologous Recombination Between Repeat Sequences in H. pylori 26695 by the PCR-Based Method

Abstract: Helicobacter pylori infects more than half of the world's population, making it the most widespread infection of bacteria. It has high genetic diversity and has been considered as one of the most variable bacterial species. In the present study, a PCR-based method was used to detect the presence and the relative frequency of homologous recombination between repeat sequences (>500 bp) in H. pylori 26695. All the recombinant structures have been confirmed by sequencing. The inversion generated between inverted r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These include a high frequency of spontaneous mutation, gene conversion, transposition, and natural competence (Fu et al, 2014). H. pylori is missing several of the genes that are important for mismatch repair, which may result in the higher rate of spontaneous mutation (Garcia-Ortiz et al, 2011; Tomb et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include a high frequency of spontaneous mutation, gene conversion, transposition, and natural competence (Fu et al, 2014). H. pylori is missing several of the genes that are important for mismatch repair, which may result in the higher rate of spontaneous mutation (Garcia-Ortiz et al, 2011; Tomb et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to inter-strain rearrangements, H. pylori has several direct and indirect repeat sequences that can result in intragenomic rearrangements (Fu et al, 2014; Kennemann et al, 2011). These gene conversion events have been documented in at least two outer membrane protein (OMP) groups, the bab genes (Solnick et al, 2004) and the sab genes (Talarico et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…DNA recombination is one of the most important factors that lead to changes of bacterial genetic information, during which DR play an important role [ 24 , 25 , 45 ]. In this study, we found that the existence of DR is a common feature of these plasmids containing qnrD , providing the potential to form a new plasmid when needed and showing that the conserved genes could be transferred and also substituted.…”
Section: Discussionmentioning
confidence: 99%
“…In the E. coli genomes, a few TRIP1 repeats were found at the junction of flanking genes from two separate loci. This is a typical result of intra-chromosomal rearrangement caused by repeat sequences [6,43,44]. To determine the frequency and influence of chromosomal arrangement caused by TRIP1 repeats, we scanned all genomes for the relative position of the 10 flanking genes from the five loci.…”
Section: Chromosomal Rearrangements Caused By Trip1 Repeat Sequencesmentioning
confidence: 99%